The comparative reactions of 2‐cis‐4‐ansa and spiro cyclotetraphosphazenes with difunctional ligands: Structural and stereogenic properties, electrochemical, antimicrobial and cytotoxic activity studies. (11th January 2021) - Okumuş, Aytuğ; Elmas, Gamze; Kılıç, Zeynel; Binici, Arzu; Ramazanoğlu, Nagehan; Açık, Leyla; Çoşut, Bünyemin; Hökelek, Tuncer; Güzel, Remziye; Tunalı, Beste Çağdaş; Türk, Mustafa; Şimşek, Hülya
Abstract : In this study, two kinds of compounds, namely, mono‐ferrocenyl‐2‐ cis ‐4‐dichloro‐ansa‐ (2, 4‐ansa; 3 ) and mono‐ferrocenyl‐spiro‐ (spiro; 4 ) hexachlorocyclotetraphosphazenes, were obtained by the Cl replacement reaction of N4 P4 Cl8 (1 ) with an equimolar amount of sodium 3‐( N‐ ferrocenylmethylamino)‐1‐propanoxide (2 ). The reactions of 2, 4‐ansa (3 ) with excess diamines and dialkoxides resulted in the formation of ansa‐cyclotetraphosphazenes (3a–3e ). Spiro (4 ) was reacted with excess diamines and dialkoxides to give the mono‐ferrocenyl‐spiro‐cyclotetraphosphazenes (4a–4d ). Although 2, 4‐ansa (3 ) produced the dispiro (3a ) with N ‐(4‐fluorobenzyl)‐ N ′‐methylethane‐1, 2‐diamine, it afforded both monospiro (3b ) and dispiro (3c ) with N ‐(4‐fluorobenzyl)‐ N ′‐methylpropane‐1, 3‐diamine. However, spiro (4 ) yielded a trispiro (4a ) with N ‐(4‐fluorobenzyl)‐ N ′‐methylethane‐1, 2‐diamine and 2, 6‐dispiro (4b ) with N ‐(4‐fluorobenzyl)‐ N ′‐methylpropane‐1, 3‐diamine. The structures of the phosphazenes were elucidated by FTIR, ESI‐MS and/or HRMS, spectroscopic and crystallographic (for 3f and 4b ) data. Furthermore, the electrochemical findings of cyclotetraphosphazenes exhibited electrochemically reversible one‐electron oxidation of Fe‐redox centre. As an example, the chirality of 3c was investigated by 31 P NMR spectroscopy on the addition of (R)‐(+)‐2, 2, 2‐trifluoro‐1‐(9′‐anthryl)‐ethanol, chiral solvating agent (CSA). The circular dichroism (CD) (for 3d and 3e ), HPLC (for 3d, 3e and 3f ) and X‐ray (for 3f ) display that these compounds have chirality (RS′ or SR′) in the solution and solid state. This paper also focuses on the antimicrobial activities, the interactions with pBR322 DNA, in vitro anticancer activity against L929 fibroblast and MCF7 breast cells, and antituberculosis activity against Mycobacterium tuberculosis H37Rv of the cyclotetraphosphazenes. Abstract : The 2, 4‐ansa and spiro‐cyclotetraphosphazenes with excess diamines and dialkoxides gave partly and fully substituted cyclotetraphosphazenes. The syntheses, chiralities, antituberculosis and cytotoxic activities of the compounds were presented.